The black hole-bulge mass relation in the megamaser host galaxies - Ronald Läsker; Jenny E. Greene; Anil Seth; Glenn van de Ven; James A. Braatz; Christian Henkel; K. Y. Lo (IOP PUBLISHING LTD, 2022)
We present Hubble Space Telescope (HST) images for nine megamaser disk galaxies with the primary goal of studying photometric BH-galaxy scaling relations. The megamaser disks provide the highest-precision extragalactic BH mass measurements, while our high-resolution HST imaging affords us the opportunity to decompose the complex nuclei of their late-type hosts in detail. Based on the morphologies and shapes of the galaxy nuclei, we argue that most of these galaxies' central regions contain secularly evolving components (pseudo-bulges), and in many cases we photometrically identify co-existing "classical" bulge components as well. Using these decompositions, we draw the following conclusions. (1) The megamaser BH masses span two orders of magnitude (10(6) - 10(8) M-circle dot) while the stellar mass of their spiral host galaxies are all similar to 10(11)M(circle dot) within a factor of three. (2) The BH masses at a given bulge mass or total stellar mass in the megamaser host spiral galaxies tend to be lower than expected when compared to an extrapolation of the BH-bulge relation based on early-type galaxies. (3) The observed large intrinsic scatter of BH masses in the megamaser host galaxies raises the question of whether scaling relations exist in spiral galaxies.